A State-of-the-Art Review on Hybrid GFRP-Concrete Bridge Deck Systems. (30th May 2021) - Zuo, Yize; Cao, Yuqi; Zhou, Yuqi; Liu, Wei Wei
Abstract : The state-of-the-art review of hybrid GFRP-concrete systems for bridge decks is presented in this study. Previous research on the experimental work, analytical modeling, and field application on hybrid GFRP-concrete deck systems are presented, along with a variety of deck systems are discussed. Then, seven typical types of connection technology between FRP and concrete are introduced and compared. Besides, the current progress on the performance of shear connections via beam tests, pushout tests, and pullout tests are probed, respectively. Finally, general conclusions are made, identifying the need for future research.